Sosiologi Pondok Pesantren Modern : Negosiasi AI dan Otoritas Keilmuan Kiai dalam Pembelajaran Kitab Kuning - Hanifah Fitriani; Muh Hanif (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This abstract examines the negotiation between the use of artificial intelligence (AI) and the preservation of the scholarly authority of Islamic boarding schools (pesantren). Using a qualitative approach to the case study of the Darussalam Modern Islamic Boarding School in Purwokerto, this study reveals that AI integration is not adopted raw, but rather negotiated through strict institutional and methodological constraints. The research findings indicate three main things: (1) At the classroom infrastructure level, the use of AI is deliberately hampered by the pesantren's domestic regulations which strictly prohibit students from bringing smartphones to maintain learning focus; (2) Epistemologically, AI has been criticized for only providing instant (cognitive) translation results and failing to teach the “procedural thinking process” in the tradition of interpreting books in a pegon (nahwu-sharaf syntax) manner. (3) Negotiations occur at the educational actor level, where teachers position AI outside the classroom purely as a khadim (technical servant) for initial reference guides that must be re-verified against authoritative books. This article contributes to the sociology of Islamic education by enriching the discussion on the cultural defense strategies of traditional religious institutions in stemming the flow of modern technological instantiation. Keywords: Artificial Intelligence, Kiai Authority, Modern Islamic Boarding Schools, Yellow Books, Techno-Spiritual Negotiation